Health Education on Mother's Baby Massage Skill - Intan Renata Silitonga; Sarah Sri Rahayu (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Baby massage has a lot of health benefits for infants and mothers, but the lack of mothers’ skills makes them not doing baby massage. This study aimed to know the effect of health education on the mother’s baby's massage skills. The method was quasi-experimental design, a one-group pre-test-post test, purposive sampling, and the total sample was 53 subjects. The study was located in Cihanjuang Rahayu Village Parongpong District in July 2021. Inclusion criteria were a mother with a baby aged 3-12 months old that stayed at Cihanjuang Rahayu Village area, with a healthy baby, and a term birth history. Exclusion criteria were the mother that refused to join the study and the mother absent during the study. The result was an increment of skill average after health education that was 82,98%, with a p-value=0,000 using paired sample t-test. The conclusion of this study is that there were significant effects of health education on the increment of mothers’ baby massage skills.